2011
DOI: 10.1111/j.1600-0447.2011.01762.x
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of executive dysfunctions in unipolar major depressive disorder without psychotic symptoms and their changes during antidepressant treatment

Abstract: We revealed significant executive dysfunctions in patients with unipolar, non-psychotic MDD compared with healthy controls and an improvement of the Stroop performance during the course of treatment. Future studies with different test procedures are needed to further investigate the influence of antidepressant treatment on executive functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
115
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(125 citation statements)
references
References 46 publications
7
115
0
3
Order By: Relevance
“…In cluster 2, a combined evaluation of both sets of results indicates that, while participants showed poorer cognitive performance than that observed in cluster 1, the most marked alterations are limited to the TMT and the semantic verbal fluency task. These alterations are consistent with the literature, which has reported significant impairments on the TMT as well as verbal fluency tasks in both BD and MDD (Bourne et al, 2013;Wagner et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…In cluster 2, a combined evaluation of both sets of results indicates that, while participants showed poorer cognitive performance than that observed in cluster 1, the most marked alterations are limited to the TMT and the semantic verbal fluency task. These alterations are consistent with the literature, which has reported significant impairments on the TMT as well as verbal fluency tasks in both BD and MDD (Bourne et al, 2013;Wagner et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…This is biologically plausible because MR expression is highest in the hippocampus and prefrontal cortex, two brain areas crucial for memory and executive function. Of note, memory and executive function are among those domains that are most consistently impaired in depressed patients (Rock et al, 2013;Wagner et al, 2012). Indeed, it has been repeatedly shown that depressed patients exhibit decreased MR expression in hippocampus and prefrontal cortex in post-mortem studies (Klok et al, 2011a;Medina et al, 2013;Qi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…GR are distributed throughout the brain and have a low affinity for cortisol, whereas MR have a high cortisol affinity and are expressed primarily in limbic areas. Both receptors are abundantly expressed in the hippocampus and in the prefrontal cortex, brain areas critical for memory and executive function (Rock et al, 2013;Trivedi and Greer, 2014;Wagner et al, 2012). Lately, animal and human studies have revealed the existence of a membrane-bound MR-mediating rapid non-genomic effects with an intermediate cortisol affinity (Henckens et al, 2011;Joels et al, 2013;van Ast et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This finding may be interpreted as trait phenomenon (or scar from a previous depressive episode) or as being due to greater depression severity. Many studies have demonstrated that attentional bias to emotional content can be found in remitted patients, whether on antidepressant treatment or not (Joormann & Gotlib, 2007; Nagane et al., 2014; Paelecke‐Habermann et al., 2005; Teasdale & Dent, 1987), but findings are still mixed (Epp et al., 2012; Wagner et al., 2012). In line with the trait hypothesis, women on antidepressant treatment reported lower scores of self‐rated depression than the depressed women who managed without pharmacological treatment, suggesting the majority were in remission when tested.…”
Section: Discussionmentioning
confidence: 99%